Relationship between waist circumference and random blood glucose level in healthy young adults - Arlizan Baizura, Ariffin; Syah Jahan Putera, Ahmad; Jessica Lim, Hui Min; Nur Aina Fariesya, Sofian; Anarina, Thomas; Norashikin, Samsudin; Madzlifah, Ahadon (2025)
Obesity has been strongly linked to metabolic diseases including type 2 diabetes mellitus (T2DM). The prevalence of obesity in young adults is increasing globally. Although body mass index (BMI) reflects general obesity, it fails to capture abdominal fat, a key predictor of insulin resistance and diabetic risk. Waist circumference (WC) is a simple anthropometric measurement for assessment of body composition and associated health risks, including T2DM. This study aimed to investigate the association between WC and random blood glucose (RBG) level in healthy young adults.